The design of external reference pricing schemes and the choice of reference countries and pricing rules - Laura Birg (Canadian Journal of Economics/Revue canadienne d'économique, 2024)
Abstract External reference pricing imposes a price cap for drugs based on prices in other countries. I study the choice of reference countries and pricing rules in a three-country framework. If the manufacturer sells to all three countries, the minimum price rule yields the lowest drug price. If the referencing country is sufficiently large, the manufacturer may not export to reference countries under the minimum price rule. External reference pricing creates the incentive for the reference countries also to adopt external reference pricing. Thus, external reference pricing results in price convergence.
Keywords: 330